History as a formative subject: epistemological and historiographical reflections - Gómez Carrasco, Cosme Jesús; Rodríguez Pérez, Raimundo A. (REVISTA DE HISTORIOGRAFÍA (RevHisto), 2017)
The traditional separation between historical research and history teaching implies that the advances of both disciplines have no real meaning. History as an educator of elites and creator of identities has given way to a civic and democratic education, which in Spain is still in its early stages. This paper sets out to analyse the evolution of historiography to find points in common with its didactic aspect. Getting students and society to view history as science requires overcoming positivism and factual history.